The Impact of Sea Ice on Cruise Tourism on Svalbard - Bystrowska, Marta (ARCTIC, 2019)
This paper explores the relationship between sea ice conditions and cruise tourism activities in the Arctic Archipelago of Svalbard. It analyzes how cruise tourism planning and organization depend on sea ice conditions and to what extent Arctic climate change influences tourism. A mixed-method approach, including sea ice analysis and interviews with 13 cruise tourism stakeholders, was applied to grasp the complexity of Svalbard’s cruise tourism. The outcomes show that cruise traffic depends on the sea ice cover, but only to some extent. Other factors, such as a location’s attractiveness or sailing regulations also influence cruise itineraries around Svalbard. Sea ice conditions are in general considered favorable for cruising around Svalbard, and sea ice is a not a decisive factor in cruise planning and organization. The sea ice cover around Svalbard is decreasing; thus, high annual and inter-annual unpredictability of sea ice poses challenges for cruise operations around Svalbard. Flexibility in itineraries, plus good cooperation and management help the cruise industry adjust to any challenges arising from uncertain sea ice conditions. However, issues of overcrowding and decreased attractiveness due to disappearing ice are more and more visible and may challenge the development of cruise tourism around Svalbard in the future. Cet article porte sur la relation qui existe entre l’état de la glace de mer et les activités du tourisme de croisière dans l’archipel arctique du Svalbard. Il se penche sur la manière dont la planification et l’organisation du tourisme de croisière dépendent de l’état de la glace de mer ainsi que sur l’ampleur de l’influence du changement climatique de l’Arctique sur le tourisme. Pour comprendre la complexité du tourisme de croisière du Svalbard, nous avons adopté une méthode à plusieurs volets, dont l’analyse de la glace de mer et des entretiens avec 13 organismes de tourisme de croisière. Cette étude a permis de déterminer que le trafic de croisière dépend de la couverture de glace de ...